Molecular cloning and functional analysis of flavanone 3-hydroxylase (f3h）gene in Passiflora edulis Sims (Bangladesh Journal of Botany, 2023)
Flavanone 3-hydroxylase (F3H) plays a crucial role in the biosynthesis of flavonoids. In the present study, one F3H gene (P_edulia040010337.g) from Passiflora edulis Sims, which has a coding sequence (CDS) of 1161 bp, encoding a protein consisting of 386 amino acid residues was cloned. The PeF3H protein contains a non-heme dioxygenase (DIOX-N superfamily) domain and a typical F3H protein functional domain (2OG-FeII-Oxy dioxygenase). Phylogenetic analysis revealed that the PeF3H protein shared high similarity with F3H proteins in Turnera subulata, Populus alba, and Populus tomentosa, with 88% identities of amino acid sequences. The PeF3H protein lacks a transmembrane structure, indicating it is likely to be expressed in the mitochondria. Additionally, 3D structure, protein and protein interaction, and KEGG pathway of PeF3H were anticipated based on homologous proteins. qRT-PCR analysis showed that PeF3H was highly expressed in leaves, followed by stems and roots. These studies have provided insights into the molecular mechanisms underlying flavonoid biosynthesis and predicted potential targets for genetic engineering to improve the nutritional and medicinal properties of passion fruit.Bangladesh J. Bot. 52(2): 613-623, 2023 (June) Special